Parental Grants to Children and Their Relation to Inheritance in the Perspective of Positive and Customary Laws of Indonesia - Afriani, Ikhfa Nur; Syah, Rohman; Avita, Nur (Al-Bayyinah, 2023)
The understanding of the correlation between parental grants (hibah) to children and inheritance can lead to disputes and conflicts among heirs within families in Indonesia. This article aims to elucidate the correlation between gifts and inheritance, particularly parental gifts to children, from the perspective of positive law and customary law in Indonesia. To achieve this, the author conducted a literature review to examine and analyze various relevant sources on gifts and their correlation with inheritance. This study yielded the following conclusions: Firstly, according to the Civil Code (KUHPerdata), Compilation of Islamic Law (KHI), and customary law, gifts given by parents to children can be counted as part of the inheritance. Secondly, the status of a child who is a recipient of parental gifts, according to the Civil Code, KHI, and customary law, does not hinder them from receiving their rightful inheritance.